2023
DOI: 10.1097/aog.0000000000005477
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of Sepsis Screening Tools During Delivery Admissions

Elliott K. Main,
Matt Fuller,
Vesela P. Kovacheva
et al.

Abstract: OBJECTIVE: To evaluate the screening performance characteristics of existing tools for the diagnosis of sepsis during delivery admissions. METHODS: This was a case–control study using electronic health record data, including vital signs and laboratory results, for all delivery admissions of patients with sepsis from 59 nationally distributed hospitals. Patients with sepsis were matched by gestational age at delivery in a 1:4 ratio with patients without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Given its significant contribution to maternal mortality, the detection and prevention of sepsis in pregnant and postpartum patients remains a key area of research. The retrospective case-control study by Main et al 1 These screening tools demonstrated a variable false-positive rate (6.9-11.6%), which increased when including patients with concomitant chorioamnionitis or endometritis. However, these statistical evaluations were calculated in a population with a fixed 20% prevalence of sepsis due to the 4:1 matching.…”
Section: Performance Characteristics Of Sepsis Screening Tools During...mentioning
confidence: 99%
See 2 more Smart Citations
“…Given its significant contribution to maternal mortality, the detection and prevention of sepsis in pregnant and postpartum patients remains a key area of research. The retrospective case-control study by Main et al 1 These screening tools demonstrated a variable false-positive rate (6.9-11.6%), which increased when including patients with concomitant chorioamnionitis or endometritis. However, these statistical evaluations were calculated in a population with a fixed 20% prevalence of sepsis due to the 4:1 matching.…”
Section: Performance Characteristics Of Sepsis Screening Tools During...mentioning
confidence: 99%
“…McDermott and Pier and Mr. Beltran for drawing attention to the challenges of screening for obstetric sepsis as outlined in our article in the March 2024 issue. 1 The concern for low specificity was addressed in the accompanying Editorial, 2 and we focused on it in our discussion. Obstetric sepsis is rare but appears to be more common than the authors note.…”
Section: In Replymentioning
confidence: 99%
See 1 more Smart Citation
“…In this month's issue of Obstetrics & Gynecology , Main et al 6 (see page 326) report the performance of pregnancy-adjusted sepsis screening tools in recognizing sepsis cases during delivery hospitalizations in 59 hospitals in the United States. The authors evaluated the screening criteria of five widely used sepsis screening systems.…”
mentioning
confidence: 99%
“…McDermott and Pier and Mr. Beltran for drawing attention to the challenges of screening for obstetric sepsis as outlined in our article in the March 2024 issue. 1 The concern for low specificity was addressed in the accompanying Editorial, 2 and we focused on it in our discussion. Obstetric sepsis is rare but appears to be more common than the authors note.…”
mentioning
confidence: 99%